Model Pendidikan Non-Formal Berbasis Komunitas Sanggar Bimbingan Permai untuk Pendidikan Anak Imigran Indonesia di Penang- Malaysia - Ismawati Saragih; Warto Warto (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study is entitled Community-Based Non-Formal Education Model of PERMAI Guidance Center for Indonesian Immigrant Children in Penang, Malaysia. This center is an educational facility for Indonesian immigrant children in Malaysia who do not have official citizenship documents. This study uses a qualitative method with a case study approach. The purpose of this study is to determine the education model used by the PERMAI Guidance Center as a community-based non-formal education institution for Indonesian immigrant children in Malaysia. The theory used in this study is the concept of Community-Based Non-Formal Education (PBK). The results of the study show that the educational curriculum used by the PERMAI Guidance Center is the Equivalency Education Curriculum (Packages A, B, and C). This curriculum is a non-formal education system equivalent to formal education (Package A is equivalent to elementary school, Package B is equivalent to junior high school, and Package C is equivalent to high school) recognized by the Ministry of Education and Culture of the Republic of Indonesia. The adoption of this curriculum is the main pillar for providing legitimacy and recognition of the education received by immigrant children at the PERMAI Guidance Center. Meanwhile, the education model used reflects the theory of transnationalism. This is manifested in two key aspects, namely the preservation of identity and the curriculum of the country of origin, as well as functional needs in the host country.